2020
DOI: 10.4143/crt.2019.713
|View full text |Cite
|
Sign up to set email alerts
|

Ramosetron versus Palonosetron in Combination with Aprepitant and Dexamethasone for the Control of Highly-Emetogenic Chemotherapy-Induced Nausea and Vomiting

Abstract: Original ArticlePurpose The purpose of this study was to compare ramosetron (RAM), aprepitant (APR), and dexamethasone (DEX) [RAD] with palonosetron (PAL), APR, and DEX [PAD] in controlling highlyemetogenic chemotherapy (HEC)-induced nausea and vomiting. Materials and MethodsPatients were randomly assigned (1:1) to receive RAD or PAD:RAM (0.3 mg intravenously) or PAL (0.25 mg intravenously) D1, combined with APR (125 mg orally, D1 and 80 mg orally, D2-3) and DEX (12 mg orally or intravenously, D1 and 8 mg ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The full text of the 25 remaining articles was reviewed in further detail, and eight more articles were excluded for the following reasons: systematic review and meta-analysis, [ 8 , 19 , 20 ] no outcome of interest [ 21 ], performed for chemotherapy-induced nausea and vomiting [ 22 , 23 , 24 ], and not a RCT [ 25 ]. The kappa value for selecting articles between the two investigators was 0.930.…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the 25 remaining articles was reviewed in further detail, and eight more articles were excluded for the following reasons: systematic review and meta-analysis, [ 8 , 19 , 20 ] no outcome of interest [ 21 ], performed for chemotherapy-induced nausea and vomiting [ 22 , 23 , 24 ], and not a RCT [ 25 ]. The kappa value for selecting articles between the two investigators was 0.930.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, ramosetron was used instead of palonosetron [ 31 ]. However, in a recent prospective randomized clinical trial that compared ramosetron and palonosetron in patients receiving HEC in Korea, it was found that ramosetron was not inferior to palonosetron in both efficacy and safety and the quality of life [ 32 ]. Therefore, our study results will be meaningfully applied to the current daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Ramosetrona, em combinação com aprepitanto e dexametasona, se mostrou tanto eficaz quanto seguro quando comparado com a palonosetrona em combinação com aprepitanto e dexametasona (Kang et al, 2020) Estudos de fase 2 para o fosaprepitanto e de fase 3 para o rolapitanto demonstram um controle melhorado de NVIQ nas fases tardia e geral quando estes fármacos são adicionados a um regime padrão de antagonista de receptor 5-HT3 (Kumagai et al, 2018;Rojas & Slusher, 2015). A esse regime também foi adicionado a dexametasona, demonstrando eficácia, segurança e tolerabilidade dessa tríade (Ahmed et al, 2018;Schwartzberg et al, 2015).…”
Section: Combinação Dos Antagonistas Do Receptor De Serotonina Com Antagonistas Do Receptor De Neurocinina E/ou Dexametasonaunclassified